Media Freedom in the Shadow of a Coup. Issue 3 (29th August 2020) - Boleslavsky, Raphael; Shadmehr, Mehdi; Sonin, Konstantin
Abstract: Popular protests and palace coups are the two domestic threats to dictators. We show that free media, which informs citizens about their rulers, is a double-edged sword that alleviates one threat, but exacerbates the other. Informed citizens may protest against a ruler, but they may also protest to restore her after a palace coup. We develop a model in which citizens engage in a regime-change global game, and media freedom is a ruler's instrument for Bayesian persuasion, used to manage the competing risks of coups and protests. A coup switches the status quo from being in the ruler's favor to being against her. This introduces convexities in the ruler's Bayesian persuasion problem, causing her to benefit from an informed citizenry. Rulers tolerate freer press when citizens are pessimistic about them, or coups signal information about them to citizens.